2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30744
|View full text |Cite
|
Sign up to set email alerts
|

K-5 Teachers' Perceptions of Engineering Education and Perceived Barriers to Teaching Engineering

Abstract: Rebekah currently serves as an Albert Einstein Distinguished Educator Fellow in the Division of Research on Learning in Formal and Informal Settings at the National Science Foundation and will join the faculty at Montana State University at the completion of her fellowship. She has spent the past 12 years teaching secondary science and engineering in Oklahoma, and is a 2014 recipient of the Presidential Award for Excellence in Mathematics and Science Teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…This study suggests that engaging elementary PSTs in science methods courses incorporating engineering design activities significantly improves their EDTE and EDE. These findings align with prior studies that found that engaging PSTs in engineering activities can enhance their engineering teaching efficacy [16,29,31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study suggests that engaging elementary PSTs in science methods courses incorporating engineering design activities significantly improves their EDTE and EDE. These findings align with prior studies that found that engaging PSTs in engineering activities can enhance their engineering teaching efficacy [16,29,31].…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that their self-efficacy in teaching engineering improved as a result. Hammack and Yeter [31] engaged elementary PSTs in multiple engineering design activities throughout the semester and found significant improvements in their engineering teaching efficacies.…”
Section: Conceptual Framework: Self-efficacymentioning
confidence: 99%
“…Other studies have reported that participating in engineering professional development opportunities has a positive impact on the engineering teaching efficacy of preservice teachers (Fogg-Rogers et al, 2017;Perkins Coppola, 2019;Smetana et al, 2019) and in-service teachers (Crawford et al, 2021;Utley et al, 2019). Further, preservice teachers who engaged in multiple engineering learning activities within a K-8 science methods course, have significantly higher engineering teaching efficacy and outcome expectancy than prior to engaging in the course (Hammack and Yeter, 2022).…”
Section: Current State Of Engineering Education In Elementarymentioning
confidence: 94%
“…One fading away with each grade level and the other emerging only in recent years as a legitimate content area. The Texas Education Agency added the Engineering essential knowledge and skills in 2015 and, while engineering is now a recognized subject, many K-5 teachers, especially, do not feel prepared to integrate engineering into their pedagogy [2].…”
Section: Introductionmentioning
confidence: 99%